High entropy materials frontier and theoretical insights for logistics CO2 reduction and hydrogenation: Electrocatalysis, photocatalysis and thermo-catalysis - Shaikh J.S. (2023)
High entropy materials (HEMs) offer excellent chemical stability, corrosion resistance, excellent mechanical properties, and good thermal stability, making them beneficial for modern catalysis technologies. Recently, HEMs have sparked interest in exploring entropy systems to advance catalysis. High-entropy-stabilized catalysts offer excellent opportunities to tune the structures, various properties, and electronic structures of HEMs. The presence of various metal species within the lattice, made possible through increased entropic involvement, exponentially enhances the tuning of catalytically active sites. Also, the presence of lattice distortion in HEMs lowers system energy, and as a consequence, it facilitates the activation and transportation of active sites. Nowadays, different types of HEMs have been investigated such as high entropy alloys (HEAs), oxides, carbides, nitrides, diborides, silicides, phosphides, sulfides, zeolites, metal-organic frameworks (MOFs), and fluorides in the field of catalysis. Adjusting the elemental composition, configuration, and structures of HEMs leads to the development of improved catalysts and helps address challenges faced by conventional and simpler catalyst systems. This review encompasses recent advancements in HEMs-based electrocatalysis, photocatalysis, and thermocatalysis for CO2 reduction and hydrogenation. The conversion of CO2 molecules into value-added products helps close the CO2 cycle and promotes a greener environment. In this review, we provide a comprehensive overview, including basic definitions of HEMs, the various types of HEMs, their advancements in the field of CO2 conversion, and theoretical insights.